2009
DOI: 10.14411/eje.2009.059
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of gene expression between the diapause initiation and maintenance phases of the Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae)

Abstract: Abstract. The diapause initiation and maintenance phases of the Colorado potato beetle, Leptinotarsa decemlineata, were screened. Eight transcripts were found to be downregulated as the beetles enter the diapause maintenance phase of diapause development after day 15 postemergence. These transcripts were also expressed in early nondiapausing adults. Using BlastX, the transcripts were placed into six broad categories: regulatory (serpin), structural (apidermin), protease (serine protease), retinol binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…It is conceivable that Bt intoxication might have consequences for the expression of genes underlying cuticular functions as a part of the metabolic arrest response, affecting timing of moulting and distribution of developmental stages. In Colorado potato beetle the transition from a state of high metabolic rates and active feeding to very low metabolic rates, no feeding, and very little movement when the beetle enters diapause is characterized by a differential regulation of cuticular protein transcripts [49], [50].…”
Section: Resultsmentioning
confidence: 99%
“…It is conceivable that Bt intoxication might have consequences for the expression of genes underlying cuticular functions as a part of the metabolic arrest response, affecting timing of moulting and distribution of developmental stages. In Colorado potato beetle the transition from a state of high metabolic rates and active feeding to very low metabolic rates, no feeding, and very little movement when the beetle enters diapause is characterized by a differential regulation of cuticular protein transcripts [49], [50].…”
Section: Resultsmentioning
confidence: 99%
“…We expected the food‐processing related metabolic genes Cys and βGlu to be down‐regulated in beetles preparing for diapause (Tauber et al ., ; Saunders, ; Hahn & Denlinger, ; Yocum et al ., ; ). However, our results were not in accordance with this expectation as the expression of Cys did not differ between the populations or photoperiods (Figs , ).…”
Section: Discussionmentioning
confidence: 99%
“…We also chose four stress tolerance genes ( HSP70A , HSP70B , DP1 , DAT2 ) and two genes with metabolic functions ( Cys , βGlu ). DP1 , DAT2 , Cys and βGlu are known to be associated with diapause in L. decemlineata (Yocum, ; Yocum et al ., , ), whereas the association of the other genes with diapause in this species is unknown. Our secondary objective was to investigate the physiological function of diapause‐associated genes by comparing gene expression with physiological traits in individual beetles.…”
Section: Introductionmentioning
confidence: 91%
“…This is very significant since glycogen is also mobilized for the production of cryoprotectant molecules and an absence of change in the maximum activity of midgut amylase in O. bicornis during winter time can be associated with activity of enzymes mobilizing glycogen. A slightly different pattern of amylase activity was exhibited in Colorado potato beetle, L. decemlineata (Yocum et al 2009a). Analysis of gene transcripts encoding particular types of amylases showed differences between the initial and maintenance phase of diapause.…”
Section: Physiological Adjustments During Overwintering In O Bicornismentioning
confidence: 91%
“…In Colorado potato beetle, Leptinotarsa decemlineata, protease activity substantially differs between the initiation and maintenance phases of diapause. Analysis of serine protease transcripts showed low expression of gene encoding the protease during initiation phase of diapause and relatively high expression from the start of maintenance phase (Yocum et al 2009a). Furthermore, it was demonstrated that genes encoding enzymes needed to digest a blood meal (trypsin and a chymotrypsin-like protease) are downregulated in diapause-destined Culex pipiens females (Robich and Denlinger 2005).…”
Section: Physiological Adjustments During Overwintering In O Bicornismentioning
confidence: 99%